The stock market reaction to credit rating changes : a multi-perspective approach - Sacchi, Vittorio (2024)
This dissertation examines the US stock market reaction to Credit Rating Changes by Standard & Poor’s, focusing on both Downgrades and Upgrades across different Time Periods, Magnitudes, and Industries. Using a rating dataset of 6,985 US public companies between 1985 and 2021, my research aims to identify patterns in stock returns around the Rating Change event. The study calculates Average Abnormal Returns (AAR) for three distinct periods: the month before the change, the month of the change, and the month after the change. Including distinction between Investment Grade and Speculative Grade securities. Downgrades consistently show negative abnormal returns, particularly in the months before and during the change. While Upgrades tend to generate milder reactions, with positive returns often observed in the month before and during the change, suggesting market anticipation. Slightly negative reactions are noticed in the month after the positive change, probably indicating market corrections. Results also stronger market reactions during economic downturns, with Speculative Grade securities showing higher volatility compared to Investment Grade ones. Additionally, the study confirms that larger magnitude changes result in stronger reactions, especially for Downgrades. The industries analysis, based on SIC and NAICS classifications, reveals variations in market sensitivity, with certain industries exhibiting reacting louder than others. Overall, this thesis contributes to the literature by adding evidence of the impact of Credit Rating Agencies on Stocks prices.